The bioavailability of furosemide-polyethylene glycol (PEG 4000) solid dispersion in male rabbits - Ellies Tianti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
Furosemide is a potential diuretic drug usually used for the secondary treatment of hypertension. Unfortunately this agent is very slightly soluble in water, so it has poor bioavailability. The oral administration of drug shows that only 60 % of the dose can be absorbed.The aim of the present study is to increase the bioavailability of furosemide by mixing the furosemide-PEG 4000 solid dispersion (1 : 1) in capsule dosage forms (formula A). The powder of LasixR tablet in capsules was used as a standard reference (formula B), and the original powder of furosemide in capsules was used as control (formula C). All of the formulas contained 40 mg of furosemide.The bioavailability of these formulas was evaluated following oral administration in male rabbits using The Latin Square Cross Over Design, then the plasma furosemide concentrations were analyzed spectrofluorometrically. The results indicated that the bioavailability of furosemide in the formula A was equal to that of the formula B (P > 0,05) or both formulas were bioequivalent. But the Cpmax value of the formula C was significantly lower in comparison with the formulas A and B.Key words: furosemide, solid dispersion, bioavailability.